BI’AH ARABIYAH DAN PENGEMBANGAN MAHARAH AL- KALAM DI PERGURUAN TINGGI ISLAM - Nuryani Nuryani (Jurnal Bahasa Lingua Scientia, 2011)
One of the challenges in teaching Arabic at school and universities is developing the language milieu or language exposure. The language exposure, both in the classroom or outside the classroom, will determine the learners’ success in mastering the Arabic language. This article discusses the efforts of two different institutions in developing the language milieu. Those institutions are Modern Islamic Boarding School Gontor and Islamic Boarding School of UIN Malang.